Forger Family’s Double Lives in Spy x Family (2022): A Psychoanalytic Approach - Susan Oktaviana; Dwi Nur Cahyani Sri Kusumaningtyas (Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores the psychological dynamics of double lives as depicted in the Forger family in Spy x Family (2022). Using a descriptive qualitative approach and applying Sigmund Freud’s psychoanalytic theory of id, ego, and superego, this research analyses how the characters of the Forger Family (Loid, Yor, and Anya) construct and negotiate their identities while maintaining concealed roles. Data were collected from selected scenes, dialogues, and character interactions in the first season of the series. The analyses reveal that Loid is driven by ego and rationality; Yor reflects the struggle between id and social morality; and Anya represents the tension between desire, self-control, and moral development, while their concealed identities simultaneously generate psychological tensions that shape and influence their interpersonal relationships. This study highlights the relevance of psychoanalytic perspectives in understanding how concealed identities influence emotional dynamics in fictional family structures.